Tuned aperture computed tomography (TACT) : an investigation on the factors associated with its image quality for caries detection - De Abreu, Murillo Jose Nunes (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--University of Stellenbosch, 2001.